Performance Feedback to Increase Use of Counseling Skills - Finai, Jalin K.; Muñoz, Karen; Ong, Clarissa W.; Butcher, Grayson M.; Nelson, Lauri; Twohig, Michael P. (Seminars in Hearing, 2018)
Counseling is a critical component of audiological care and when implemented purposefully can yield multiple benefits for patients. Professional guidelines indicate that counseling is within the scope of practice for audiologists, yet research has shown that audiologists feel unprepared and are not comfortable providing adjustment counseling. This may be due to inadequate counseling training in audiology graduate programs. To identify ways to address this counseling training gap, this study examined the use of performance feedback to increase counseling skills among audiology graduate students. In this study, participants (n = 5) were recorded during clinical session encounters, and recordings were coded for time spent counseling. A licensed clinical psychologist reviewed the recordings and provided individual performance feedback to participants over the course of the study. Time spent counseling increased by the end of the study, although improvement varied across participants. Results suggest that performance feedback can be used as a method to increase counseling skills in audiology students. However, factors, such as participant motivation, feedback timing, and prerequisite counseling skills, may influence response to feedback. More research is needed on ways to maximize gains from feedback, as well as other methods to improve counseling skills in audiology students.
Keywords: Counseling; audiology; performance feedback